A STUDY OF APPLICATION ON NPV-AT-RISK MODEL AS A TOOL FOR INVESTMENT EVALUATION IN TOLL ROAD INFRASTRUCTURE PROJECT (CASE STUDY: THE DEVELOPMENT OF CISUMDAWU TOLL ROAD) - FITRIANI (NIM : 250 03 061); Pembimbing : Dr. Ir. Puti Farida Marzuki; Dr. Ing Andreas Wibowo, HENI
Strategic capital investment decisions are crucial and require careful analysis and consideration. These are all because the characteristics of infrastructure projects that are vulnerable to risks and uncertainties. NPV-at-Risk model developed by Ye and Tiong (2000) as a tool for investment evaluation under uncertainties, formerly was applied on cases with fictive cash flows using many assumption parameters. It becomes important for the writer to study and apply this model in the real case, using more representative parameters so that the problems found by applying this model and future recommendation can be known. This model will be applied on Cisumdawu toll road phase I as the case study, the segment of Cileunyi-Tanjungsari-Sumedang recommended by Sumedang Regency. The basic principle of this model is to measure the return and risk separately in stochastic analysis. Weighted Average Cost of Capital (WACC) is used as discount rate to discount the cash flows of the project. By applying this model, the probabilities of NPV and risk variability can be known. Finally this model can give a much more attractive and varying recommendation especially for the investors to do the investment decision.